Relationship between pathogenic E.coli O78-induced intestinal epithelial barrier damage and Zonulin expression levels in yaks - Ren, Xiaoli; Shi, Bin; Chang, Zhenyu; Zhang, Jingbo; Wang, Shuo; Liu, Ruidong; Sang, Mudan; Dong, Hailong (Frontiers in Cellular and Infection Microbiology, 2024)
To explore whether the intestinal damage of yak colibacillosis resulted from the regulation of Zonulin expression by its pathogenic bacteria, the overexpression and interference plasmids of Zonulin were designed and cultured in Tranwell after cell transfection. Then qRT-PCR and Western blot were used to detect the results of cell transfection, 200 mL 1×105 CFU/mL E.coli O78 was added for 4 hours, transmembrane resistance was measured by transmembrane resistance meter, FD4 fluorescence concentration in the lower chamber was detected by enzyme labeling instrument, bacterial translocation was measured by CFU counting method, and epithelial mucin (MUC1, MUC2) and tight junction protein (FABP2, Occludin, ZO-1) were detected by qRT-PCR.ResultsThe Zonulin gene overexpression and knockout cell lines were successfully constructed, the TEER value of the barrier of Zonulin overexpression cell lines began to decrease at 1 h after the addition of E.coli O78 and reached the lowest value at 4 h, and the TEER value of Zonulin interference cell lines decreased within 1-4 h after the addition of E.coli O78. At 4 h, the FD4 passing capacity of Zonulin overexpression cell lines was significantly higher than that of interfering cell lines, reaching twice as much as siRNA-1. The amount of bacterial translocation in overexpressed cell lines increased rapidly within 1-4 h, and the concentration of E.coli in the lower chamber was significantly higher than that in the siRNA-1 group at 4 h, but there was no significant change in the siRNA-1 group in the 1-4 h. There was no significant change in the mRNA level of MUC1 in Zonulin overexpression and interference cell lines after the addition of E.coli O78. In the overexpression group, the mRNA levels of MUC2, Occludin, and ZO-1 were significantly decreased, and the mRNA level of FABP2 was increased considerably. These results suggest stimulate epithelial cells to secrete Zonulin protein. Many Zonulin proteins regulate the opening of tight junction structures, reduce the transmembrane resistance of the cell barrier, and improve the permeability of the cell barrier and the amount of bacterial translocation.